Use of optical motion capture for the analysis of normative upper body kinematics during functional upper limb tasks: A systematic review - Valevicius, A. M.; Jun, P. Y.; Hebert, J. S.; Vette, A. H. (Journal of Electromyography and Kinesiology, 2018)
Quantifying three-dimensional upper body kinematics can be a valuable method for assessing upper limb function. Considering that kinematic model characteristics, performed tasks, and reported outcomes are not consistently standardized and exhibit significant variability across studies, the purpose of this review was to evaluate the literature investigating upper body kinematics in non-disabled individuals via optical motion capture. Specific objectives were to report on the kinematic model characteristics, performed functional tasks, and kinematic outcomes, and to assess whether kinematic protocols were assessed for validity and reliability. Five databases were searched. Studies using anatomical and/or cluster marker sets, along with optical motion capture, and presenting normative data on upper body kinematics were eligible for review. Information extracted included model characteristics, performed functional tasks, kinematic outcomes, and validity or reliability testing. 804 publication records were screened and 20 reviewed based on the selection criteria. Thirteen studies described their kinematic protocols adequately for reproducibility, and 8 studies followed International Society of Biomechanics standards for quantifying upper body kinematics. Six studies assessed their protocols for validity or reliability. While a substantial number of studies have adequately reported their protocols, more systematic work is needed to evaluate the validity and reliability of existing protocols.